MENTAL NURSING CARE MR. U WITH THE RISK OF VIOLENT BEHAVIOR AT THE PEKANBARU TAMPAN MENTAL HOSPITAL IN 2022 - Kiki Rizki Dasaryandi; Dedy Asep; Anggi Ngesti Rahayu (Pusat Riset dan Inovasi Nasional, 2022)
Schizophrenia is a mental disorder that can end in the loss of a person's life. In handling this disease because the soul is disturbed, it is needed therapy, rehabilitation and counseling. The greatest effort to deal with mental disorders lies in the family and community, in this case the best therapy is a form of family support in preventing the recurrence of schizophrenia. In people with schizophrenia, there can be physical aspects of increased blood pressure, increased pulse and breathing, anger, irritability, tantrums and can injure themselves. Changes in cognitive, physiological, affective, to behavioral and social functions to cause the risk of violent behavior. This KIAN aims to provide an overview of Mental Nursing Care for Schizophrenic Patients at Risk of Violent Behavior. Violent behavior is a response to stressors faced by a person, this response can cause harm to oneself, others, and the environment. The function of the strategy for implementing violent behavior is to control the emotions of the hallucinations experienced by the client.